2008
DOI: 10.1021/la801252t
|View full text |Cite
|
Sign up to set email alerts
|

Surface Acoustic Wave Biosensor as a Tool to Study the Interaction of Antimicrobial Peptides with Phospholipid and Lipopolysaccharide Model Membranes

Abstract: Surface acoustic wave biosensors are a powerful tool for the study of biomolecular interactions. The modulation of a surface-confined acoustic wave is utilized here for the analysis of surface binding. Phase and amplitude of the wave correspond roughly to mass loading and viscoelastic properties of the surface, respectively. We established a procedure to reconstitute phospholipid and lipopolysaccharide bilayers on the surface of a modified gold sensor chip to study the mode of action of membrane-active peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…The results shown are representative of three independent experiments. The SAW biosensor system (Biosensor GmbH, Bonn, Germany) was used as described before (1). Briefly, in the SAW biosensor a SAW is propagated along a sensor surface and the modification of its phase and amplitude induced by binding of molecules to the surface is a measure for mass adsorption and change of viscoelastic properties, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The results shown are representative of three independent experiments. The SAW biosensor system (Biosensor GmbH, Bonn, Germany) was used as described before (1). Briefly, in the SAW biosensor a SAW is propagated along a sensor surface and the modification of its phase and amplitude induced by binding of molecules to the surface is a measure for mass adsorption and change of viscoelastic properties, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We immobilized LPS onto carboxymethylated dextran (CM3) chips and used surface plasmon resonance (SPR) to monitor interactions (Fig. 4A) (33). When chips derivatized with LPS are subjected to injections of polymyxin B, a cyclic LPS-binding peptide (34), it remained on the surface as indicated by the change in mass adhered to the chip (measured in resonance units), whereas RNase A, known to recognize other negatively charged sugars, is not retained by LPS.…”
Section: Positively Charged Residues At the Extracellular Side Of Lptmentioning
confidence: 99%
“…Although earlier reports suggested that LPS modulates bacterial cell compressibility and helps prevent catastrophic structural failure due to mechanical stress (1,52), no direct physical evidence of its involvement in these processes has yet been presented. Therefore, monitoring biofilm viscoelasticity is crucial for demonstrating how well biofilms resist stresses, due to, for instance, fluid shear and antimicrobial peptides (5,6). To date, quantitative data on how LPS affects viscoelastic properties of biofilms are lacking, and existing studies have merely focused on elasticity measurements (7,52).…”
mentioning
confidence: 99%